Clinical outcomes and risk factors for posterior reversible encephalopathy syndrome in systemic lupus erythematosus: a multicentric case–control study. Issue 3 (24th March 2015) - Merayo-Chalico, Javier; Apodaca, Elia; Barrera-Vargas, Ana; Alcocer-Varela, Jorge; Colunga-Pedraza, Iris; González-Patiño, Alejandra; Arauz, Antonio; Abud-Mendoza, Carlos; Martínez-Martínez, Marco; Gómez-Martín, Diana
Abstract : Background: Posterior reversible encephalopathy syndrome (PRES) is a well-known but rare complication in patients (<1%) with systemic lupus erythematosus (SLE). However, current epidemiological data are quite scant. The aim of the present study was to describe potentially unrecognised risk factors. Patients and methods: We performed a multicentre, retrospective case–control study in Mexico between 1999 and 2014. We included a total of 168 patients who accounted for 77 episodes of PRES, as follows: SLE/PRES, 43 patients with 48 episodes; SLE without PRES, 96 patients; and PRES without SLE, 29 patients. SLE diagnosis was considered when patients fulfilled ≥4 American College of Rheumatology criteria. PRES was defined by reversible neurological manifestations and MRI changes. Results: Patients with SLE/PRES were younger, presented with seizures as the most common manifestation (81%) and 18% had the typical occipital MRI finding. Hypertension (OR=16.3, 95% CI 4.03 to 65.8), renal dysfunction (OR=6.65, 95% CI 1.24 to 35.6), lymphopenia (OR=5.76, 95% CI 1.36 to 24.4), Systemic Lupus Erythematosus Activity Index ≥ 6 points (OR=1.11, 95% CI 1.01 to 1.22) and younger age (OR=0.86, 95% CI 0.81 to 0.91, p<0.001) were independent risk factors for development of PRES in SLE. Furthermore, dyslipidemia also characterised the association between PRES and SLE (OR=10.6, 95% CI 1.17 to 96.4). Conclusions: This is the largest reported series of patients with SLE and PRES. We were able to corroborate the known risk factors for of PRES, and found two previously undescribed factors (lymphopenia and dyslipidemia), which suggests that endothelial dysfunction is a key element in PRES pathogenesis in lupus patients.